Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s11136-011-9898-3
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Epworth Sleepiness Scale in Central China

Abstract: PurposeThe well-known excessive daytime sleepiness (EDS) assessment, Epworth Sleepiness Scale (ESS), is not consistently qualified for patients with diverse living habits. This study is aimed to build a modified ESS (mESS) and then to verify its feasibility in the assessment of EDS for patients with suspected sleep-disordered breathing (SDB) in central China.MethodsA Ten-item Sleepiness Questionnaire (10-ISQ) was built by adding two backup items to the original ESS. Then the 10-ISQ was administered to 122 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 18 publications
1
25
0
1
Order By: Relevance
“…Furthermore, the lifestyles and economic backgrounds of the populations in these two regions differ from those in Mainland China. Zhang et al [42] and Peng et al [43] have also developed two simplified Chinese versions of the ESS. In the former study, the researchers created a modified ESS by adding two backup items to the original ESS and forming a ten-item Sleepiness Questionnaire; however, this practice might have changed the original meaning of the scale.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the lifestyles and economic backgrounds of the populations in these two regions differ from those in Mainland China. Zhang et al [42] and Peng et al [43] have also developed two simplified Chinese versions of the ESS. In the former study, the researchers created a modified ESS by adding two backup items to the original ESS and forming a ten-item Sleepiness Questionnaire; however, this practice might have changed the original meaning of the scale.…”
Section: Discussionmentioning
confidence: 99%
“…Given cultural differences in lifestyle, inaccuracy of the ESS based on evidence in previous studies has been suggested. 37 , 38 The number of people who drive themselves in automobiles is much smaller in Korea than in Western countries, especially among women and the elderly. Furthermore, the floor living lifestyle in Korea and Japan is different from the lifestyle of sitting in a chair in China and Western countries.…”
Section: Methodsmentioning
confidence: 99%
“…[1314] Although uniformity in the questionnaires across the population, ethnic group, and languages is important to maintain comparability, variability due to the irrelevance of a question does become a dominant issue. Hence, customizing the question according to the population being tested is important.…”
Section: Discussionmentioning
confidence: 99%
“…[14] The authors of that study observed a poor response to the item 8 question and attributed this to the lack of driving experience among almost 75% of their patients. In this Chinese study also, modifications were added to the scale, based on the sociocultural characteristics of their population.…”
Section: Discussionmentioning
confidence: 99%